LUBAC Formation Is Impaired in the Livers of Mice with MCD-Dependent Nonalcoholic Steatohepatitis - Yasuka Matsunaga; Yusuke Nakatsu; Toshiaki Fukushima; Hirofumi Okubo; Misaki Iwashita; Hideyuki Sakoda; Midori Fujishiro; Takeshi Yamamotoya; Akifumi Kushiyama; Shin-ichiro Takahashi; Yoshihiro Tsuchiya; Hideaki Kamata; et al. (Hindawi Limited, 2015)
Nonalcoholic steatohepatitis (NASH) is a disorder characterized by hepatic lipid accumulation followed by the inflammation-induced death of hepatocytes and fibrosis. In this process, oxidative stress contributes to the induction of several inflammatory cytokines including TNF-α and　IL-1β in macrophages, while, in hepatocytes, NF-κB reportedly induces the expressions of cell survival genes for protection from apoptosis. Recently, it was reported that the new ubiquitin ligase complex termed linear ubiquitin chain assembly complex (LUBAC), composed of SHARPIN (SHANK-associated RH domain-interacting protein), HOIL-1L (longer isoform of heme-oxidized iron-regulatory protein 2 ubiquitin ligase-1), and HOIP (HOIL-1L interacting protein), forms linear ubiquitin on NF-κB essential modulator (NEMO) and thereby induces NF-κB pathway activation. In this study, we demonstrated the formation of LUBAC to be impaired in the livers of NASH rodent models produced by methionine and choline deficient (MCD) diet feeding, first by either gel filtration or Blue Native-PAGE, with subsequent confirmation by western blotting. The reduction of LUBAC is likely to be attributable to markedly reduced expression of SHARPIN, one of its components. Thus, impaired LUBAC formation, which would result in insufficient NF-κB activation, may be one of the molecular mechanisms underlying the enhanced apoptotic response of hepatocytes in MCD diet-induced NASH livers.